Indicators of global sustainable sourcing as a set covering problem: an integrated approach to sustainability. Issue 2 (27th April 2015) - Huber, Patrick R.; Springer, Nathaniel P.; Hollander, Allan D.; Haden, V. Ryan; Brodt, Sonja; Tomich, Thomas P.; Quinn, James F.
Abstract : Sustainability describes a broad set of themes centered on current human uses of the planet's resources. The multiple uses and users of the term have led to a proliferation of salient issues and associated indicators. We present a new method to systematically link these issues and indicators under two conceptual frameworks of sustainability in order to enable quantitative analyses. We demonstrate this approach with a specific use case focused on the global sourcing of agricultural products. We use the optimization software Marxan in a novel way to develop minimum sets of indicators that provide maximum coverage of sustainability issues. Minimum covering sets were identified and accumulation curves were developed to measure the contribution of each indicator in each set to overall issues coverage. While greater detail in the assessment of each indicator would likely provide more effective sets of indicators, those that were generated provide optimism that this approach can bring better focus to sustainability assessments.